A gadofullerene based liver-specific MRI contrast agent for an early diagnosis of orthotopic hepatocellular carcinoma. Issue 28 (6th July 2021) - Zhao, Zhongpu; Zhen, Mingming; Zhou, Chen; Li, Lei; Jia, Wang; Liu, Shuai; Li, Xue; Liao, Xiaodan; Wang, Chunru
Abstract : Hepatocellular carcinoma has become one of the most prevalent cancers, with a high mortality rate. Abstract : Hepatocellular carcinoma has become one of the most prevalent cancers, with a high mortality rate. Accurate diagnosis at an earlier stage is regarded as an effective measure to reduce the disease-related mortality of liver cancer. Magnetic resonance imaging (MRI) as a non-invasive checking mode has become a powerful tool in medical diagnosis. However, MRI contrast agents for liver-specific imaging either have some side effects or the imaging effect is not ideal. Thus, development of more efficient and security MRI contrast agents for the early diagnosis of hepatocellular carcinoma is urgent. Herein, a kind of water-soluble gadofullerene nanoparticle (GFNP) with high efficiency and security has been successfully used to achieve in situ liver cancer imaging. By comparing GFNPs with different functional groups, Gd@C82 modified by a hydroxyl group (GF-OH) presents the highest contrast efficiency both in vitro and in vivo . Notably, the smallest tumor with a diameter of only 0.5 mm could be clearly observed by GF-OH using MRI. Moreover, the imaging window of GF-OH is more than 3–6 hours. In addition, GF-OH can be mostly excreted from the living body and causes no serious toxicity. These results demonstrate that GF-OH is a safe, efficient MRI contrast agent for the diagnosis of early orthotopic hepatocellular carcinoma.